2016
DOI: 10.1021/acschembio.6b00290
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Dehydrogenase C Produces S-2-Hydroxyglutarate in Mouse Testis

Abstract: Metabolomics is a valuable tool for studying tissue- and organism-specific metabolism. In normal mouse testis, we found 70 μM S-2-hydroxyglutarate (2HG), more than 10-fold greater than in other tissues. S-2HG is a competitive inhibitor of α-ketoglutarate-dependent demethylation enzymes and can alter histone or DNA methylation. To identify the source of testis S-2HG, we fractionated testis extracts and identified the fractions that actively produced S-2HG. Through a combination of ion exchange and size exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 40 publications
4
42
0
Order By: Relevance
“…S5A). In agreement with earlier studies (16,21), we also observed that human LDHA catalyzed the reaction of 2OG to L-2HG, thereby demonstrating that LDH generates L-2HG via an evolutionarily conserved enzymatic mechanism ( Fig. 3B and Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…S5A). In agreement with earlier studies (16,21), we also observed that human LDHA catalyzed the reaction of 2OG to L-2HG, thereby demonstrating that LDH generates L-2HG via an evolutionarily conserved enzymatic mechanism ( Fig. 3B and Fig.…”
Section: Resultssupporting
confidence: 92%
“…2 D and E). Furthermore, these metabolic defects were specifically due to the loss of dLDH activity, as the aberrant pyruvate, lactate, and 2HG levels observed in dLdh 16 /dLdh 17 mutants were completely rescued by a dLdh transgene (Fig. 2 D and E).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations